Observational evidence of deep convection over Indonesian sector in relation with major stratospheric warming events of 2003–04 and 2005–06 - Sridharan, S.; Sathishkumar, S. (My University, 2011)
The major sudden stratospheric warming (SSW) events of 2003–04 and 2005–06 are considered to investigate changes in equatorial convection due to circulation changes associated with the SSW events. It is observed that the SSW events are accompanied by a considerable decrease in Outgoing Longwave Radiation (OLR), a proxy for tropical convection, over equatorial latitudes (15°N–15°S) in the Indonesian sector (90°E–150°E). However, unlike noted by earlier observations, the zonal mean OLR does not show any notable relationship with the SSW events. It can be explained from the latitude–longitude map of potential vorticity (PV) at 100 hPa, which shows a tongue of high PV emanating from high latitudes towards equator and converges in the longitude band of 90°E–150°E on the day of peak warming at 1 hPa in the case of 2003–04 and 10 hPa in the case of 2005–06. The latitude-height map of Eliassen–Palm (EP) vector and its divergence show convergence of EP flux in the upper troposphere at latitudes even lower than 20°N on these days. Further, vertical winds computed from the convergence of momentum flux are upward indicating convective activity at low-latitudes and downward at mid-latitudes.
Keywords: Startospheric warming; Equatorial convection; Eliassen–Palm flux; Indonesian sector; SSW; Outgoing Long wave Radiation; OLR; Middle atmosphere